Study of the genetic diversity of tomato (Solanum spp.) with ISSR markers - Eider Echeverry Vargas, John; Ceballos Aguirre, Nelson; Morillo Coronado, Yacenia (Revista Ceres, 2025)
In this study 55 tomato genotypes from different geographical regions were evaluated with ISSR markers (Inter Simple Sequence Repeats). The seven ISSR primers originated 63 amplified bands, of which 90.48% were polymorphic. The cluster analysis based on the Nei-Li similarity coefficient using the average genetic clustering method (UPGMA) revealed the conformation of five clusters at a level of similarity of 72%. The ISSR technique did not discriminate tomato genotypes according to the species or region of provenance. The structure analysis and the dendrogram did not reveal a genetic structure in the population evaluated. The genotypes of the species of S. pimpinellifolium, S. l. cerasiforme, S. lycopersicum and S. peruvianum were found consistently grouped, showing a close genetic relationship among them. A high genetic variation among the individuals within each of the groups formed was suggested by the AMOVA. The ISSR markers were effective in assessing the genetic diversity and structure of populations of tomato genotypes. The high genetic variability found in this study indicates the valuable genetic potential present in tomato germplasm, especially of wild species, which could be used for future breeding programs of the species.